Exploring the Role of Trust in the Deal–Making Process for Early–Stage Technology Ventures. (September 2013) - Scarbrough, Harry; Swan, Jacky; Amaeshi, Kenneth; Briggs, Tony
The deal–making process requires entrepreneurial actors to create and maintain wide networks of weak ties while simultaneously developing stronger collaborative ties that will enable opportunities to be realized. We currently lack an adequate account of how these activities are integrated by deal–makers under conditions of risk and uncertainty. In an empirical study of deal making in early–stage technology ventures, we find that deal–makers rely on different forms of trust in the early and later phases. Based on this study, we develop a process model and propositions on the role of trust in integrating strong and weak ties in deal making.